ChIP Display: novel method for identification of genomic targets of transcription factors - Barski, Artem (Oxford University Press, 2004)
Novel protein–DNA interactions in mammalian cells are traditionally discovered in the course of promoter studies. The genomic era presents opportunities for the reverse; namely, the discovery of novel target genes for transcription factors of interest. Chromatin immunoprecipitation (ChIP) is typically used to test whether a protein binds to a candidate promoter in living cells. We developed a new method, ChIP Display (CD), which allows genome-wide unbiased identification of target genes occupied by transcription factors of interest. Initial CD experiments pursuing target genes for RUNX2, an osteoblast master transcription factor, have already resulted in the identification of four genes that had never been reported as targets of RUNX2. One of them, Osbpl8, was subjected to mRNA and promoter–reporter analyses, which provided functional proof for its regulation by RUNX2. CD will help to assemble the puzzle of interactions between transcription factors and the genome.